Nitrogen Release in Pristine and Drained Peat Profiles in Response to Water Table Fluctuations: A Mesocosm Experiment - Merjo P. P. Laine; Rauni Strömmer; Lauri Arvola (Applied and Environmental Soil Science)
In the northern hemisphere, variability in hydrological conditions was suggested to increase as a consequence of climate warming, which may result in longer droughts than the area has experienced before. Due to their predominately anoxic conditions, peatlands are expected to respond to changes in hydrological conditions, such as successive drying and rewetting periods. As peatlands are rich in organic matter, any major changes in water table may influence the decomposition of it. The hydrological conditions may also influence release of nutrients from peat profiles as well as affect their transport to downstream ecosystems. In our mesocosm experiment, artificial water table fluctuations in pristine peat profiles caused an increase in dissolved organic nitrogen (DON) and ammonium (NH4+-N) concentrations, while no response was found in drained peat profiles, although originating from the same peatland complex.